2014
DOI: 10.15288/jsad.2014.75.929
|View full text |Cite
|
Sign up to set email alerts
|

Early Adolescent Symptoms of Social Phobia Prospectively Predict Alcohol Use

Abstract: ABSTRACT. Objective: The current study examined whether social phobia (SP) symptoms in early adolescence prospectively predicted alcohol use through middle adolescence in a community sample of youth. Method: Data from an ongoing longitudinal study (N = 277) of mechanisms of HIV-related risk behaviors in youth were used to assess the extent to which SP symptoms in early adolescence (mean [SD] age = 11.00 years [0.81]) would predict alcohol use across fi ve annual assessment waves. Adolescents completed measures… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
11
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 36 publications
2
11
0
Order By: Relevance
“…The evidence from literature in the area for social phobia, however, is inconclusive. For example, in a longitudinal study, Dahne and colleagues (2014) reported that elevated social phobia symptoms predicted higher odds of alcohol use.…”
Section: Discussionmentioning
confidence: 99%
“…The evidence from literature in the area for social phobia, however, is inconclusive. For example, in a longitudinal study, Dahne and colleagues (2014) reported that elevated social phobia symptoms predicted higher odds of alcohol use.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, SAD and symptoms of social anxiety prospectively predicts AUD and substance use disorders (Buckner & Schmidt, 2009;Buckner & Turner, 2009;Buckner et al, 2008;Dahne, Banducci, Kurdziel, & MacPherson, 2014;Wolitzky-Taylor, Bobova, Zinbarg, Mineka, & Craske, 2012). Indeed, SAD and symptoms of social anxiety prospectively predicts AUD and substance use disorders (Buckner & Schmidt, 2009;Buckner & Turner, 2009;Buckner et al, 2008;Dahne, Banducci, Kurdziel, & MacPherson, 2014;Wolitzky-Taylor, Bobova, Zinbarg, Mineka, & Craske, 2012).…”
Section: Introductionmentioning
confidence: 98%
“…The above-mentioned studies provide less evidence for a direct effect from AUD to SAD (Buckner & Turner, 2009;Dahne et al, 2014;Wolitzky-Taylor et al, 2012). Nevertheless, from a psychopharmacological perspective, it is likely that alcohol use produces anxiety, at least during withdrawal, and a few studies indicate that AUD causes anxiety (Becker, 2012;Fergusson, Boden, & Horwood, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Childhood and adolescent anxiety often follows a chronic trajectory and persists into adulthood (Beesdo, Knappe, & Pine, 2009), where it is associated with a host of adverse consequences (e.g., poor health, social and work impairment; Aderka et al, 2012; Ramsawh, Stein, Belik, Jacobi, & Sareen, 2009; Stein et al, 2005) and significant economic burden (Baxter, Vos, Scott, Ferrari, & Whiteford, 2014). In addition to anxiety disorders, increased anxiety symptoms in early adolescence have been associated with future psychopathology and poorer outcomes (Bosquet & Egeland, 2006; Cole, Peeke, Martin, Truglio, & Seroczynski, 1998; Dahne, Banducci, Kurdziel, & MacPherson, 2014; McLaughlin & King, 2015). To address this major public health concern research has begun to focus on early identification and prevention, and one way this has been accomplished is through a better understanding of the etiopathogenesis of anxiety disorders and symptoms.…”
mentioning
confidence: 99%